Livsfara eller livräddare : en jämförande studie av träd på två förskolor i Lunds kommun - Olofsson, Morgan; Åvall, Hampus (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2019)
Trees are something that most of us humans have some form of connection to, both positive and negative. Research shows that an early connection to trees can benefit children’s development both in a cognitive way and develop motor skills. Trees also offer other services that humans can benefit from, especially in cities and in rural areas.